Optimised maintenance medium of Acetobacter xylinum for bacterial cellulose production / Suryani Kamarudin … [et al.] - Kamarudin, Suryani; Awang Biak, Dayang Radiah; Kalil, Mohd. Sahaid; Tey, Beng Ti (Universiti Teknologi MARA Cawangan Pahang, 2008)
The production of bacterial cellulose (BC) is very important nowadays because of its potential application in many fields. The maintenance medium was optimised to obtain a suitable medium for Acetobacter xylinum with high production of BC Two sets of medium composition are being compared which are known as the crude medium and the derived medium. The crude medium uses natural substrate as a carbon source called coconut water. The composition of the derived medium is based on a modified H-S medium using sucrose as a carbon source. Both media were cultivated for three days at 30°C under static fermentation. Analysis was done by measuring the thickness of the gel forming on the surface of the liquid medium. The result shows that the growth of cells in the crude medium was observed at as early as 24 hours of the incubation time. The approximately 4-fold production in the crude medium as compared to the derived medium was observed at 3 days' cultivation time. It was concluded that the crude medium was the optimised maintenance medium for bacterial cellulose production by Acetobacter xylinum.